2022
DOI: 10.3390/biomedicines10071622
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Conserved HLA Class I and Class II Epitopes from SARS-CoV-2 Licensed Vaccines Supports T-Cell Cross-Protection against SARS-CoV-1

Abstract: Heterologous immunity-inducing vaccines against different pathogens are necessary to deal with new pandemics. In this study, the possible impact of COVID-19 licensed formulations in the cytotoxic and the helper cellular immune responses against SARS-CoV-1 is analyzed for the 567 and 41 most abundant HLA class I and II alleles, respectively. Computational prediction showed that most of these 608 alleles, which cover >90% of the human population, contain enough conserved T-cell epitopes among SARS-CoV-1 and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…Five noteworthy variants of SARS-CoV-2 were declared by WHO as Alpha, Beta, Gamma, Delta, and Omicron (Vass et al 2022 ). SARS-CoV-2 is a virus associated with the SARS-CoV-1 virus that triggered the 2002–2004 SARS outburst (Lopez 1622 ). COVID-19 was declared a pandemic in March/2020.…”
Section: Introductionmentioning
confidence: 99%
“…Five noteworthy variants of SARS-CoV-2 were declared by WHO as Alpha, Beta, Gamma, Delta, and Omicron (Vass et al 2022 ). SARS-CoV-2 is a virus associated with the SARS-CoV-1 virus that triggered the 2002–2004 SARS outburst (Lopez 1622 ). COVID-19 was declared a pandemic in March/2020.…”
Section: Introductionmentioning
confidence: 99%
“…Common HLA allotypes can be selected using computational techniques and bioinformatics resources, such as the SYFPEITHI and NetMHCpan ( 60 63 ) algorithms, and mutation-prone regions should be removed. Many functional SARS-CoV-2-derived T-cell epitopes have been identified and require further experimental validation ( 64 66 ). For effective B-cell epitope selection, the three-dimensional structure of the epitope is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we used in silico approaches to overcome this challenge of herd immunity by analyzing the 600 most common HLA alleles covering > 90% of the world’s population regardless of ethnicity. We found that each of these most frequent HLA alleles could be able to present around 4-5 epitopes shared by SARS-CoV-1 and SARS-CoV-2 ( 8 ). Supporting our results, the scarce available data from slightly more than 200 SARS-CoV patients (limited to most prevalent and frequent HLA alleles) were highly concordant (91%) with our predicted epitopes ( 8 ).…”
mentioning
confidence: 94%
“…We found that each of these most frequent HLA alleles could be able to present around 4-5 epitopes shared by SARS-CoV-1 and SARS-CoV-2 ( 8 ). Supporting our results, the scarce available data from slightly more than 200 SARS-CoV patients (limited to most prevalent and frequent HLA alleles) were highly concordant (91%) with our predicted epitopes ( 8 ). Because HLA genes are tightly linked in the genome, each individual expresses 6 to 12 different alleles (6 per chromosome) in a Mendelian fashion.…”
mentioning
confidence: 94%
See 1 more Smart Citation